(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes conditional constructions in the Japanese language from a functional-semantic perspective. The study examines the grammatical structure, usage conditions, and semantic nuances of the forms 〜ば, 〜たら, 〜なら, 〜と, 〜ても, たとえ〜ても, 〜さえ〜ば, and 〜ては. These constructions are classified into semantic groups such as real condition, hypothetical condition, concessive condition, and intensified (emphatic) condition. The article provides a comparative analysis of the differences between similar forms, particularly 〜ば and 〜たら, 〜なら and 〜たら, as well as 〜ても and 〜ば. Special attention is given to the construction 〜さえ〜ば as an expression of minimal condition, and to 〜ては as a form associated with undesirable or negative results. The research concludes that Japanese conditional constructions differ not only in grammatical form but also depending on context, logical relations, and the speaker’s subjective attitude. The findings contribute to a deeper understanding and more accurate use of conditional forms for students of the Japanese language.